The Values of Admiral Malahayati’s Struggle and Their Implications for the Political Culture of Coastal Communities in Lamnga Settlement, Mesjid Raya Subdistrict, Aceh Besar Regency - Izza Madani; Eny Kusdarini (International Journal of Applied Research and Innovation, 2026)
This study examines the struggle values of Laksamana Malahayati and their implications for the political culture of coastal communities in Lamnga, Aceh Besar. Employing an empirical qualitative design with a phenomenological approach, the research explores how historical values are internalized, transformed, and sustained within contemporary socio political practices. Data were collected through in depth interviews with community members, cultural observers, and local leaders, supported by document analysis and triangulation techniques. The findings reveal that values such as courage, solidarity, leadership, and social responsibility continue to shape participatory practices, collective identity, and decision making processes within the community. At the same time, globalization and modernization introduce shifts toward pragmatism and individualism, particularly among younger generations, creating a dynamic interplay between tradition and change. The study also identifies multi level strategies of value preservation involving family, community institutions, and cultural practices, as well as adaptive innovations through education and digital media. The research contributes to the theoretical understanding of political culture by conceptualizing historical values as dynamic constructs that mediate continuity and transformation in coastal societies.